Ethnically mismatched student-teacher relationships and the effects of communication. - Singleton, Taylor (Trinity College (Dublin, Ireland). School of Education, 2021)
Abstract The purpose of this research is to determine teacher understandings of student-teacher relationships (STR) and the effects of communication. The literature review focuses on defining challenging behavior and communication strategies. It uses previous findings to identify the importance of STR, as well as what effects positive and negative STR is proven to have. Many factors towards developing STR are included within the literature review to create further clarity on the research. The effects of STR on minority students are profound, as indicated by previous findings. The methodology of this work is a mixed method approach. An online survey was used to collect quantitative data. It provides individual accounts of teacher experiences and is comparable to the larger whole. A focus group was used to collect qualitative data. It provides further clarity to individual accounts found in surveys, but also reveals emerging themes within a group of participants. This research has revealed the following about the subject school in relation to teacher understandings of STR and communication: - Tardiness and talking as the two most frequently occurring and widespread challenging behavior. - Behavior initiatives are inconsistent and too frequent and therefore negatively impact how behavior in addressed in classrooms. - Teachers lack an understanding of student culture and how STR impacts students. - A demand for professional development opportunities that may improve teacher retention, teacher sanity, and student learning. Understanding may help develop ways to positively improve STR in majority-minority schools. Through this research, frequent challenging behavior and inconsistencies in understanding have been identified. Fulfilling the needs that educators have for professional development opportunities will improve understanding of student culture and ability to address challenging behavior. Further, it will improve retention and strengthen routines and learning in order to benefit both students and teachers in their relationships.
Keywords: Positive Behaviour Management; Education